BRAF inhibitor‐associated cutaneous squamous cell carcinoma: new mechanistic insight, emerging evidence for viral involvement and perspectives on clinical management. (1st October 2017) - Wu, J.H.; Cohen, D.N.; Rady, P.L.; Tyring, S.K.
Summary: Mutations in the BRAF proto‐oncogene occur in the majority of cutaneous melanomas. The commonly detected valine (V) to glutamate (E) mutation (V600E) is known to drive melanomagenesis and has thus been the target of two highly selective chemotherapeutic agents: vemurafenib and dabrafenib. While BRAF inhibitor therapy has revolutionized the treatment of metastatic melanoma, unanticipated cutaneous toxicities, including the development of cutaneous squamous cell carcinomas (cSCCs), are frequently reported and hinder therapeutic durability. However, the mechanisms by which BRAF inhibitors induce cutaneous neoplasms are poorly understood, thus posing a challenge for specific therapies. In this review, we summarize the clinical and molecular profiles of BRAF inhibitor‐associated cSCCs, with a focus on factors that may contribute to disease pathogenesis. In particular, we discuss the emerging evidence pointing towards viral involvement in BRAF inhibitor‐induced cutaneous neoplasms and offer new perspectives on future therapeutic interventions. Continued clinical and mechanistic studies along this line will not only allow for better understanding of the pathogenic progression of BRAF inhibitor‐induced cSCCs, but will also lead to development of new therapeutic and preventative options for patients receiving targeted cancer therapy.